Kajian Penerapan Media Pembelajaran Berbasis IT Dalam Meningkatkan Pemahaman Konsep Matematika Pada Materi Bangun Data di SD Negeri Gunungkembang Kabupaten Cianjur: Penelitian - Sarhindi, Sarhindi; Jamjuri, Endi; Komariah, Eneng; Lindawati, Lindawati; Setiawan, Iwan; Mardiana, Dinny (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The understanding of mathematical concepts in elementary school students, especially in the material of plane figures, is still a common problem that appears in various studies due to the abstract characteristics of the material and is difficult for students to visualize. Although information technology-based media has been widely developed, the research gap is still visible in how the application of IT media is adapted in the real context of elementary school classes, especially in areas with limited facilities such as Gunungkembang Public Elementary School. This study aims to examine the effectiveness of the use of IT-based learning media in improving students' understanding of mathematical concepts in the material of plane figures. The method used is descriptive qualitative research with data collection techniques including observation, interviews, and documentation, which are analyzed using the Miles, Huberman, and Saldana model. The results of the study show that the use of IT-based media in the form of interactive videos and animations not only improves students' conceptual understanding abilities including explaining concepts, identifying the properties of plane figures, and solving contextual problems but also creates a more interactive and conducive classroom atmosphere, so that the dynamic visualizations presented make abstract concepts more concrete and make IT media an effective learning strategy for elementary school students.